Dimensi Ketuhanan Falsafah Mashā’iyyah: Suatu Pengamatan Konseptual: Dimension of Peripatetic Divine Philosophy: A Conceptual Observation - Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2019)
The article observes Mashā’iyyah’s divine philosophical dimension which refers to the ideas of al-Kindī, al-Fārābī, Ibn Sīnā and Ibn Rushd. The discourse was dilated by Mashā’iyyah’s interaction with Aristotle’s metaphysical tradition based on the concept of effective cause (`illah) as the basis of evidence for the reality of existence. Critically, the pursuit of purification of this philosophical tradition is accomplished through the idea of harmonization of religion and philosophy (al-tawfīq bayn al-dīn wa al-falsafah). This article highlights the background of Aristotle’s idea of metaphysic, Mashā’iyyah’s idea of harmonization and its relation to the formation of their divine concept. Ironically, the study found that despite Mashā’iyyah’s efforts that were very synonymous with the tauhid’s aspiration, the divine concept was still influenced by Aristotle’s metaphysical dimension in perceiving the divine character of Allah SWT.